2015
DOI: 10.3390/ijms161125948
|View full text |Cite
|
Sign up to set email alerts
|

Notch Cooperates with Survivin to Maintain Stemness and to Stimulate Proliferation in Human Keratinocytes during Ageing

Abstract: The Notch signaling pathway orchestrates cell fate by either inducing cell differentiation or maintaining cells in an undifferentiated state. This study aims to evaluate Notch expression and function in normal human keratinocytes. Notch1 is expressed in all epidermal layers, though to a different degree of intensity, with a dramatic decrease during ageing. Notch1 intracellular domain (N1ICD) levels are decreased during transit from keratinocyte stem cells (KSC) to transit amplifying (TA) cells, mimicking survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…ChIP-seq analysis of DLX3 and H3K4me3 DNA binding domains identified DLX3-bound promoter regions of genes involved in cell cycle regulation during differentiation, such as Ccnd1, Ccne1; 41, 42 and epidermal structure, such as Clic4, Dsp, Evpl, Fabp5, 43, 44, 45, 46 and transcription factors such as Grhl3, Klf4, Msx2 and Notch1 47, 48, 49, 50 (Figure 8). Together with the transcriptomic analysis, the ChIP-seq analysis of DLX3 and H4K4m3 binding supports a potential DLX3-dependent transcriptional regulation of these genes during epidermal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-seq analysis of DLX3 and H3K4me3 DNA binding domains identified DLX3-bound promoter regions of genes involved in cell cycle regulation during differentiation, such as Ccnd1, Ccne1; 41, 42 and epidermal structure, such as Clic4, Dsp, Evpl, Fabp5, 43, 44, 45, 46 and transcription factors such as Grhl3, Klf4, Msx2 and Notch1 47, 48, 49, 50 (Figure 8). Together with the transcriptomic analysis, the ChIP-seq analysis of DLX3 and H4K4m3 binding supports a potential DLX3-dependent transcriptional regulation of these genes during epidermal differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been shown that SOX2 regulates self-renewal and tumorigenicity of human melanoma-initiating cells [46]. Of note, Notch1 cooperates with survivin to maintain stemness and stimulates proliferation of human keratinocytes [47]. Taken together, survivin, in a large part through the Hedgehog/GLI pathway, substantially contribute to the pro-oncogenic activities including stemness in human cancer.…”
Section: Survivin Expression Hedgehog/gli Signaling Pathway and Canmentioning
confidence: 99%
“…While scramble transfected cells grow exponentially with time, survivin depleted cells display a slow rate of proliferation, as shown by vital cell analysis ( Figure 1 A), and give rise to a significantly lower amount of colonies with bigger size ( Figure 1 B,C). In association with the short and long term proliferative potential, survivin expression knocking-down in cSCC primary cells correlates with the decreased expression of stemness-associated markers, such as OCT-4, NOTCH1, CD133 and β 1 -integrin [ 22 , 28 , 29 , 30 , 31 ] ( Figure 1 D). Interestingly, NOTCH1-survivin axis in the maintenance of human keratinocyte stemness [ 30 ] appears to be preserved also in the context of tumor cells.…”
Section: Resultsmentioning
confidence: 98%
“…In association with the short and long term proliferative potential, survivin expression knocking-down in cSCC primary cells correlates with the decreased expression of stemness-associated markers, such as OCT-4, NOTCH1, CD133 and β 1 -integrin [ 22 , 28 , 29 , 30 , 31 ] ( Figure 1 D). Interestingly, NOTCH1-survivin axis in the maintenance of human keratinocyte stemness [ 30 ] appears to be preserved also in the context of tumor cells. On the other hand, the expression of early epidermal differentiation markers, such as keratin 10 (K10) and involucrin, was increased ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 98%